2013
DOI: 10.1016/j.janxdis.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Information processing bias and pharmacotherapy outcome in older adults with generalized anxiety disorder

Abstract: Information processing bias was evaluated in a sample of 25 older adults with generalized anxiety disorder (GAD) over the course of 12 weeks of escitalopram pharmacotherapy. Using the CANTAB Affective Go/No Go test, treatment response (as measured by the Hamilton Anxiety Rating Scale, Penn State Worry Questionnaire, and Generalized Anxiety Disorder Severity Scale) was predicted from a bias score (i.e., difference score between response latencies for negative and positive words) using mixed-models regression. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Research into (bio)marker-based prediction of the therapy response, tolerability, and side effects can be helpful in individually tailoring treatment of late-life anxiety, extending available evidence in early and mid-life anxiety disorders [48]. For instance, based on a study by Steiner et al [40], a more positive processing bias might serve as a marker of the treatment response to escitalopram in old-age GAD. Furthermore, a pharmacogenetic study in late-life anxiety suggest that the 5-HTTLPR/ rs25531 genotype modulates the therapeutic efficacy of escitalopram [15].…”
Section: Personalized Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into (bio)marker-based prediction of the therapy response, tolerability, and side effects can be helpful in individually tailoring treatment of late-life anxiety, extending available evidence in early and mid-life anxiety disorders [48]. For instance, based on a study by Steiner et al [40], a more positive processing bias might serve as a marker of the treatment response to escitalopram in old-age GAD. Furthermore, a pharmacogenetic study in late-life anxiety suggest that the 5-HTTLPR/ rs25531 genotype modulates the therapeutic efficacy of escitalopram [15].…”
Section: Personalized Treatmentmentioning
confidence: 99%
“…Accordingly, processing bias was evaluated in a sample of 25 older adults with GAD during a 12-week treatment with escitalopram. Steiner et al [40] found that a more positive bias score across time predicted a better treatment response. Faster responses to positive words relative to negative words were associated with greater symptomatic improvement over time as reflected by scores on the GADSS.…”
Section: Pathomechanisms Of Anxiety In Late Lifementioning
confidence: 99%
“…This pattern is typically shown by patients with affective disorders, whereas the opposite pattern is shown by healthy subjects ( Erickson et al , 2005 ). Furthermore, in anxiety patients, the negative bias in reaction time on AGN was shown to predict worse response to a 12-week psychopharmacological treatment, whereas a positive bias predicted symptom improvement following treatment ( Steiner et al , 2013 ). These results confirm that using AGN can reliably capture negative biases in attention, and identify potential links of such biases with impaired control and mechanisms underlying anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it remains unclear whether the involvement of the posterior IFC in negative affective bias can be detected at the structural level and, if so, whether it also reflects individual differences in anxiety levels. The present study examined the relations among the gray matter volume of pars opercularis, trait anxiety, and the negative affective bias measured by AGN, and tested the following hypotheses: (1) Trait anxiety is positively associated with measures of negative bias ( Steiner et al , 2013 ), and negatively associated with measures of opercular volume ( Shang et al , 2014 ); (2) Opercular volume is negatively associated with negative bias ( Brown et al , 2012 ); (3) In line with the proposed relations between opercular volume and trait anxiety, and between trait anxiety and negative bias, we also explored the possibility that trait anxiety mediates the relation between volumetric measures of pars opercularis and measures of negative bias ( Fales et al , 2010 ).…”
Section: Introductionmentioning
confidence: 99%